1985
DOI: 10.1172/jci111910
|View full text |Cite
|
Sign up to set email alerts
|

Primate mammary development. Effects of hypophysectomy, prolactin inhibition, and growth hormone administration.

Abstract: The pituitary gland has been found to be an important factor in mammary development in primates. Hypophysectomy in 12 sexually immature monkeys caused significant inhibition of estradiol (E2)-induced mammary growth and development. A histological index of mammary development in sexually immature hypophysectomized animals was lower (0.82) than in intact E2-treated controls (3.4; P < 0.008). Hypophysectomy also inhibited growth of the mammary gland as judged by a size index. Despite the hypophysectomy, E2 stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
2

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 27 publications
0
19
0
2
Order By: Relevance
“…Subsequently, Silastic capsules providing follicular-phase levels of E2 were implanted subcutaneously (5). Mean weekly E2 concentrations in serum were 141.5 ± 10.9 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, Silastic capsules providing follicular-phase levels of E2 were implanted subcutaneously (5). Mean weekly E2 concentrations in serum were 141.5 ± 10.9 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Although prolactin (PRL) has been assumed to be the principal mammogenic pituitary hormone, a number of indirect lines of experimental evidence have placed in doubt the role of PRL in mammary mitogenesis, inferentially supporting the possibility that the pituitary may contain other mammogenic factors (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Triply-operated rodents require administration of oestrogen intact non-pregnant animals. In sexually immature monkeys, hypophysectomy inhibits the growth and development of the mammary gland stimulated by oestradiol, but neither prolactin nor G H was confidently identified as the pituitary factor involved (Kleinberg et al 1985). Some of the hormonal activities involved in mammary development may originate in the placenta in pregnant females.…”
Section: Endocrine Control Of Postnatal Mammary Developmentmentioning
confidence: 96%
“…We found that lactogenic as well as nonlactogenic forms of GH are far more potent than PRLs from the same species in inducing mammary development in assays employing hypophysectomized, castrated, and estradiol (E2)-treated, sexually immature rats (12). Moreover, mammary development was not impaired in rhesus monkeys in which PRL secretion was maximally inhibited (13). In recent experiments, we also found that only those naturally occurring or mutant lactogens or somatogens that avidly bind to GH receptors in rat liver are potent inducers of the initial mammary differentiation and development (14).…”
mentioning
confidence: 95%